A machine learning approach to analyse ozone concentration in metropolitan area of Lima, Peru - Natalí Carbo‐Bustinza; Marisol Belmonte; Vasti Jimenez; Paula Montalban; Magiory Rivera; Fredi Gutiérrez Martínez; Mohamed Mehdi Hadi Mohamed; Alex Rubén Huamán De La Cruz; Kleyton da Costa; Javier Linkolk López‐Gonzales (My University, 2022)
The main objective of this study is to model the concentration of ozone in the winter season on air quality through machine learning algorithms, detecting its impact on population health. The study area involves four monitoring stations: Ate, San Borja, Santa Anita and Campo de Marte, all located in Metropolitan Lima during the years 2017, 2018 and 2019. Exploratory, correlational and predictive approaches are presented. The exploratory results showed that ATE is the station with the highest prevalence of ozone pollution. Likewise, in an hourly scale analysis, the pollution peaks were reported at 00:00 and 14:00. Finally, the machine learning models that showed the best predictive capacity for adjusting the ozone concentration were the linear regression and support vector machine.
Keywords: Metropolitan area; Support vector machine; Ozone; Exploratory analysis; Machine learning; Population; Air pollution; Environmental science; Air quality index; Cartography; Geography; Computer science; Environmental health; Meteorology; Medicine; Data science; Biology; Ecology; Archaeology; Metropolitan area; Support vector machine; Ozone; Exploratory analysis; Machine learning; Population; Air pollution; Environmental science; Air quality index; Cartography; Geography; Computer science; Environmental health; Meteorology; Medicine; Data science; Biology; Ecology; Machine Learning; Machine Learning; Machine Learning; Machine Learning; Air Pollutants analysis; Air Pollutants analysis; Air Pollutants analysis; Air Pollutants analysis; Air Pollution analysis; Air Pollution analysis; Air Pollution analysis; Air Pollution analysis; Environmental Monitoring methods; Environmental Monitoring methods; Environmental Monitoring methods; Environmental Monitoring methods; Ozone analysis; Ozone analysis; Ozone analysis; Ozone analysis; Peru; Peru; Peru; Peru; Physical Sciences Environmental Science Environmental Engineering Air Quality Monitoring and Forecasting; Physical Sciences Environmental Science Health, Toxicology and Mutagenesis Air Quality and Health Impacts; Physical Sciences Environmental Science Global and Planetary Change COVID-19 impact on air quality